Proposal for standardized ultrasound analysis of the salivary glands: Part 1 submandibular gland - Henry T. Hoffman; Michael Koch; Robert Lee Witt; William R. Ryan; Johannes Zenk; Philippe Katz; Rahmatullah Rahmati; Christopher Rassekh; Francisco Donato; Timothy M. McCulloch; Arjun S. Joshi; Jolie Lien Chang; et al. (Laryngoscope Investigative Otolaryngology, 2024)
Abstract Objectives The Salivary Gland Committee of the American Academy of Otolaryngology‐Head and Neck Surgery seeks to standardize terminology and technique for ultrasonograpy used in the evaluation and treatment of salivary gland disorders. Methods Development of expert opinion obtained through interaction with international practitioners representing multiple specialties. This committee work includes a comprehensive literature review with presentation of case examples to propose a standardized protocol for the language used in ultrasound salivary gland assessment. Results A multiple segment proposal is initiated with this focus on the submandibular gland. We provide a concise rationale for recommended descriptive language highlighted by a more extensive supplement that includes an extensive literature review with additional case examples. Conclusion Recommendations are provided to improve consistency both in performing and reporting submandibular gland ultrasound.